Phyllagathis chongzuoensis (Melastomataceae), a new species from Guangxi, China - Zhang, Zhe; Tu, Xiong-De; Yao, Shi-Wei; Ma, Liang; Zeng, Si-Jin (Phytotaxa, 2021)
Phyllagathis chongzuoensis, a new species from Guangxi Province, China, is described here. It is similar to P. erecta in having stiffly papery leaf blades with abaxially furfuraceous indumentum, similar leaf vernation, umbellate paniculate inflorescences and cup-shaped capsules, but differs in stoloniferous stem with indistinct internodes, shorter petioles, and obovate to suborbicular leaf blades with irregularly denticulate margin. Phylogenetic analyses based on nrITS and plastid genome confirmed that it is close to P. erecta.